Covalent immobilization of α-CGTase on cellulose nanofiber derived from kenaf bast for enzymatic membrane reactor - Sulaiman, Safwan (2018)
Nanobiocatalyst is a new frontier of emerging nano-sized material support in enzyme immobilization application. This approach provides an innovative strategy between enzyme technology and utilization of natural nano-cellulose support in nanobiotechnology. This research work was focused on the covalent immobilization of α-cyclodextrin glucanotranferase (α-CGTase) on the cellulose nanofiber (CNF) support from kenaf bast fiber. The obtained immobilized α- CGTase-CNF was applied in stirred-cell ultrafiltration (UF) membrane system as enzymatic membrane reactor (EMR). Chemical-physical treatment (e.g. delignification, 3-stage of bleaching and high-intensity ultrasonication) were firstly performed to isolate the CNF from kenaf bast fiber. The combination of this treatment contributes to the efficiency of hemicellulose and lignin removal, and reduce its size from micro to nano-order. SEM and TEM analysis show the size distribution of fiber in a range of nano-order scale (<100 nm), which higher ultrasonication output power resulted in smaller size of CNF. Chemical composition analysis reveals the cellulose content increased up to 90% after the treatment. FTIR analysis reveals the changes in the surface functional group of CNF, contributes successful in removal of lignin and hemicellulose in the fiber. FTIR analysis also confirms successful immobilization of α-CGTase on CNF through ligand–spacer arm interaction (α-CGTase–GA–1,12-diaminododecane– CNF), where there is no significant damages on the dimensional structural of fiber after went through these treatments process. The efficiency of immobilized α-CGTase shows more than 62% of binding yield and more than 45% of its residual activity were obtained. The membrane fouling of α-CGTase-CNF layer using UF membrane indicated to the higher permeate flux declined when applying higher pneumatic pressure to the system, but it decreased in production yield of α-CD. Reusability profile of fouled α-CGTase-CNF layer is able to retain up to 50-60% of α-CGTase activity at 10th cycle and α-CD productivity that represent for each operation cycle was slightly decreased from its initial cycle. Substrate concentration and pneumatic pressure contribute to the major effect of fouled α-CGTase-CNF layer toward the performance of membrane operation and enzymatic production yield. Permeate flux profiles indicate the lowest substrate concentration with high pneumatic pressure showed the best performance of membrane operation with lowest permeate flux declined. Meanwhile, enzymatic production of α-CD profiles indicate that higher substrate concentration with lowest pneumatic pressure contributed to the highest value of α-CD production. Mass transfer and reaction kinetic of fouled α-CGTase-CNF layer were evaluated using gPROMS software. This software was used to study the mechanism and behavior of fouled α-CGTase- CNF layer toward the effect of substrate concentration and pneumatic pressure for the performance of membrane operation and its effectiveness during enzymatic reaction. The application of enzymatic membrane reactor (EMR) module system with accuracy of mathematical modelling is beneficial for further development of continuous membrane operation system with excellent enzymatic performance and it is able to be reused for multiple times.